La ricerca nelle scuole di dottorato in Italia. Dottorandi e docenti a confronto: il Seminario SIRD - Luciano Galliani (LED Edizioni Universitarie, 2010)
Research in Graduate Schools in Italy. Doctoral Students and Teachers Exchange Views: the SIRD Seminar The article reports on a SIRD (Società Italiana di Ricerca Didattica) initiative, now in its 4th edition, consisting of a seminar with Ph.D. students and university lecturers, held in September 2010. About forty students took part (some as speakers) along with ten (senior/fellow) lecturers who had critical-educational evaluation tasks. The positive experience yielded indications for a broader reflection on the development of doctorate schools in Italy, with reference to the principles established by the European University Association (EUA) in Salzburg in 2005 and then revisited in Berlin in June 2010. In particular, the schools and doctorates in the pedagogical sphere are critically analysed in relation to their disciplinary composition with a view to guaranteeing a «critical mass and critical diversity», by focusing and developing research methodology in specific areas or domains of educational sciences, adopting internationalisation strategies, facilitating career paths, and promoting young Ph.D. graduates' access in various occupational contexts.